Comportamento dos custos da construção civil na Universidade Federal de Santa Maria - Colpo, Iliane (2016)
Federal Universities promote higher education, and for that receive funds to be administered by public managers. Especially in 2007 with the establishment of the Restructuring Program and Expansion of Federal Universities resources for investment grew, allowing universities to intensify the expansion of its physical space. To contract engineering services the public administrator must follow the rules established primarily by Federal Law 8.666/93. Following the legislation, from construction planning to conclusion, the hiring process goes through several stages. As regards the building costs, this appears mainly in three stages: in the standard budget to public competition, the ratification of the contracted company and the final stage of the building conclusion. This thesis aimed to study the behavior of the civil construction costs at the Federal University of Santa Maria from 2010 to 2014, in especially regarding the estimated costs, the granted costs and the final cost of the work. This study is justified due to the relevance of the subject, because it is the use of public resources, largely originated from taxes collected from society. The study was developed through qualitative and quantitative research, using as a way the document and literature research and a ending the descriptive research. The results show the variations between planned and executed time, with a percentage of 75.55% of the construction resulting in terms of time additives, among the main causes identifies the change or project adjustments. Regarding per m² cost variation, the contracts are separated into groups according to the characteristics of the works, showing that the group with precast construction sets has the highest percentage of bids accepted and executed that were made at lower costs than budgeted. The group of buildings is the one with the highest percentage of additives terms and due to this the greater variation between the budgeted and executed. In canceled contracts, all unilaterally by the federal government, the cause listed was the contract break on estabilished schedule.